2012
DOI: 10.1021/jm300952s
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Imidazo[4,5-b]pyridine-Based Kinase Inhibitors: Identification of a Dual FLT3/Aurora Kinase Inhibitor as an Orally Bioavailable Preclinical Development Candidate for the Treatment of Acute Myeloid Leukemia

Abstract: Optimization of the imidazo[4,5-b]pyridine-based series of Aurora kinase inhibitors led to the identification of 6-chloro-7-(4-(4-chlorobenzyl)piperazin-1-yl)-2-(1,3-dimethyl-1H-pyrazol-4-yl)-3H-imidazo[4,5-b]pyridine (27e), a potent inhibitor of Aurora kinases (Aurora-A Kd = 7.5 nM, Aurora-B Kd = 48 nM), FLT3 kinase (Kd = 6.2 nM), and FLT3 mutants including FLT3-ITD (Kd = 38 nM) and FLT3(D835Y) (Kd = 14 nM). FLT3-ITD causes constitutive FLT3 kinase activation and is detected in 20–35% of adults and 15% of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 62 publications
3
78
0
Order By: Relevance
“…28 In parallel to this work, we also investigated the design and synthesis of Aurora-A-selective inhibitors based on the imidazo[4,5- b ]pyridine scaffold. Herein, we report our medicinal chemistry program aimed at the identification of imidazo[4,5- b ]pyridine- and 7-azaindole-based inhibitors displaying a high degree of selectivity for Aurora-A over Aurora-B.…”
Section: Introductionmentioning
confidence: 99%
“…28 In parallel to this work, we also investigated the design and synthesis of Aurora-A-selective inhibitors based on the imidazo[4,5- b ]pyridine scaffold. Herein, we report our medicinal chemistry program aimed at the identification of imidazo[4,5- b ]pyridine- and 7-azaindole-based inhibitors displaying a high degree of selectivity for Aurora-A over Aurora-B.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the encouraging pre-clinical results, AT9283 is being tested in relapsed and refractory ALL and AML in a Phase I trial in the UK. A potentially important development is the discovery of compounds that inhibit both FLT3 and aurora kinases; a dual FLT3/aurora kinase inhibitor known simply as compound 27e ( 19 ) may show enhanced clinical efficacy due to synergy between FLT3 and aurora kinase inhibition (Bavetsias et al, 2012). (See Figure 2F for structures of the compounds discussed in this section.…”
Section: Molecularly Targeted Drug Discovery and Developmentmentioning
confidence: 99%
“…A plethora of early phase clinical trials are evaluating small molecule inhibitors against these kinases (reviewed in). Preclinical data have shown that inhibition of Aurora A, B and FLT3 kinase by compound 27e led to growth inhibition in an FLT3‐ITD‐positive AML xenograft . AT9283 has shown in vitro activity in cell line models for myeloproliferative disorders with gain of function mutations in JAK2 and in adult phase I/II trials for solid tumors and hematological malignancies .…”
Section: Introductionmentioning
confidence: 99%